2007
DOI: 10.1017/s1751731107000420
|View full text |Cite
|
Sign up to set email alerts
|

Tail docking in horses: a review of the issues

Abstract: Routinely performed painful procedures are of increasing interest and, in 2001 (Royal Order, May 17), Belgium prohibited docking in several vertebrates including horses. In 2004, opponents to this decision submitted a Bill (Doc51 0969/001) to Parliament, intending to obtain derogation for Belgian draught horses, which were traditionally docked. The Animal Welfare Council of Belgium, an official body advising the Minister of Public Health, was asked to evaluate this complex question, including biological, ethic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 115 publications
0
6
0
1
Order By: Relevance
“…Although considered a breach of the rules under most codes of showing, it is difficult to detect after the agent itself has been passed by defecation. Inarguably, any manipulations of horse's tail carriage or conformation (including docking) should be undertaken only when there is a sound veterinary reason (Lefebvre et al, 2007).…”
Section: Gingeringmentioning
confidence: 99%
“…Although considered a breach of the rules under most codes of showing, it is difficult to detect after the agent itself has been passed by defecation. Inarguably, any manipulations of horse's tail carriage or conformation (including docking) should be undertaken only when there is a sound veterinary reason (Lefebvre et al, 2007).…”
Section: Gingeringmentioning
confidence: 99%
“…For example, tail docking is a procedure by which the distal tail vertebrae are amputated. It occurs in large numbers of horses for aesthetic reasons, but recently this practice has been challenged because it causes unnecessary pain and health risks to the animals (Lefebvre et al, 2007). Although there are arguments (Lefebvre et al, 2007) that docking improves a horse's hygiene and welfare, the results of our study suggest that shortening the tail length would inhibit a horse's ability to shoo away hazardous biting insects.…”
Section: Discussionmentioning
confidence: 69%
“…Tails in mammals serve many purposes, including defense, balance, communication and locomotion (Hickman, 1979). Many investigators have assumed that the tail is used to defend against insects (Mooring et al, 2007;Hickman, 1979;Samuel et al, 2001;Lefebvre et al, 2007;Siegfried, 1990), as shown in Fig. 1A.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure is more linked to habits based on cultural (aesthetics and increased value) and technical objectives (Lefebvre et al, 2007) than to concerns on production quality or animal health. In this case, there may be more reluctance from defenders to give up tail docking, but laws prohibiting tail docking and the discrediting of horses with a docked tail in shows and sales from professional organisations encourages its disappearance (Lefebvre et al, 2007). Additional arguments can also be found when the procedure can be proven to have further disadvantages than evoking pain.…”
Section: Introductionmentioning
confidence: 99%